Adoption of near field communication in S-Library application for information science - Mohd Kamir, Yusof; Mohd Nordin, Abdul Rahman; Andrew, Abel (Emerald Group Holdings Ltd., 2015)
Purpose – The purpose of this paper is to first review the implementation of automatic identification and data capture) technologies in library/information science, focusing on barcode technology, radio frequency identification (RFID) and near field communication (NFC). This paper then presents S-Library, a new android-based application, to enable users to perform a wide range of information science-related transactions, such as borrowing, searching, returning and viewing transaction records.